Schistosoma mansoni shares a protective carbohydrate epitope with keyhole limpet hemocyanin (The Rockefeller University Press, 1987)
The glycanic epitope of the 38,000 Mr Schistosoma mansoni schistosomula major immunogen defined by the IPLSm1 protective mAb was identified in the hemocyanin of the marine mollusc Megathura crenulata, better known as KLH. This antigenic community was exploited to investigate further the biological properties of this epitope. KLH was shown to strongly inhibit the binding of IPLSm1 mAb to its 38,000 Mr target antigen. Immunization of naive LOU rats with KLH elicited the production of anti- S. mansoni antibodies capable of immunoprecipitating the 38,000 Mr schistosomulum antigen. Antibodies to KLH mediated a marked eosinophil- dependent cytotoxicity and passively transferred immunity towards S. mansoni infection. Finally, rats immunized with KLH were significantly protected against a challenge with S. mansoni cercariae. The deglycosylation of KLH completely abolishes its immunological and functional KLH properties, indicating the participation of an oligosaccharidic epitope of the native KLH that is also recognized by the sera of S. mansoni-infected patients. These observations provide new opportunities of access to the well-defined structure of a glycanic epitope potentially available for the immunoprophylaxis and seroepidemiology of schistosomiasis, and a new approach to the isotypic response towards a well-chemically defined epitope.